2009
DOI: 10.2741/3528
|View full text |Cite
|
Sign up to set email alerts
|

Methodology, biology and clinical applications of mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are adult stem cells able to give rise to mature mesenchymal cell types. Plastic-adherent cells are operationally defined as MSCs based on their ability to proliferate and differentiate into cells such as osteoblasts, adipocytes and chondrocytes. In the past ten years, cultured MSCs have been shown to exhibit great plasticity in culture, as they can differentiate into cells with ectodermal and endodermal characteristics, suggesting their use as a source of cells to treat different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 142 publications
0
60
0
1
Order By: Relevance
“…Among the various stem cell populations used for cell therapy, adult mesenchymal stem cells (MSC, also referred to as mesenchymal stromal cells) have emerged as a major new cell technology with a diverse spectrum of potential clinical applications. 1,2 At least 92 clinical trials are currently using MSC worldwide (http://clinicaltrials.gov/).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various stem cell populations used for cell therapy, adult mesenchymal stem cells (MSC, also referred to as mesenchymal stromal cells) have emerged as a major new cell technology with a diverse spectrum of potential clinical applications. 1,2 At least 92 clinical trials are currently using MSC worldwide (http://clinicaltrials.gov/).…”
Section: Introductionmentioning
confidence: 99%
“…Along with these phenotypic characteristics, MSCs secrete various anti-apoptotic, immunomodulatory, angiogenic, antiscarring, and chemoattractant bioactive molecules, providing a basis for their use as tools to create local regenerative environments in vivo. 42 Experimental and clinical data also demonstrated an immunoregulatory function of BM-derived MSC, which may contribute to the reduction of the incidence of graft versus host disease following hematopoietic stem cell transplantation.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…We have also suggested that the perivascular location of MSCs, associated to their remarkable immunoregulatory capacity, implies a role in the maintenance of tissue homeostasis: in the case of tissue injury, MSCs secrete a panel of cytokines and factors that control the immune response to avoid an autoimmune process [8]. These studies have shown that, although similar in general characteristics, MSCs isolated from different tissues, such as brain, spleen, liver, kidney, lung, bone marrow, muscle, thymus, and pancreas, exhibit particular biological features, raising the question on whether they are identical cell populations or have important differences at the molecular level [9].…”
Section: Introductionmentioning
confidence: 99%